KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp) DI KEBUN RAYA SAMBAS KECAMATAN SUBAH KABUPATEN SAMBAS KALIMANTAN BARAT - Hairunnsisah, .; Dewantara, Iswan; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2018)
Kantong semar is a type of plant that belongs to a unique plant category, the uniqueness of this plant is found in the form of a variety of follicle. The purpose of this research is to know the diversity of kantong semar (Nepenthes spp). The research used purposive sampling technique with double plot method measuring 2m x 2m. The results show that found as many as 5 types of kantong semar, namely N. ampullaria, N. rafflesiana, N. xhookeriana, N. mirabilis and N. reindwardtiana, with a total of 67 individuals. The highest index of dominance is N. ampularia with value (C = 0.128) followed by N. reindwardtiana with value (C = 0,89), N. Rafflesiana with value (C = 0,027), N. mirabilis with value (C = 0,018 ) and N. Xhookeriana with value (C = 0.002). The index of species diversity has a value (d = 2,190). The highest index of Morisita is N. Mirabillis with value (Is = 1,681), N. reindwardtiana with value (Is = 1,211), N. ampularia with value (Is = 1,174), N. xhookeriana (Is = 1,167) and N. rafflesiama with the value (Is = 1,155).Keywords: diversity, dominance, Nepenthes spp